Attitudes and Beliefs About Emergency Contraception Among Patients at Academic Family Medicine Clinics - Campbell, John W. (American Academy of Family Physicians, 2008)
PURPOSE The possible mechanisms of action of emergency contraception (EC) include preventing ovulation, fertilization, or implantation of an embryo. Differences in the use of terminology between medical personnel and the general public could be misleading to patients who would use EC. This cross-sectional survey evaluated women’s beliefs regarding pregnancy and EC’s possible mechanisms of actions. METHODS An anonymous questionnaire was developed and pilot tested for an appropriate reading level and ease of analysis. It collected information on demographics and beliefs about pregnancy and EC. During an 8-week period, the questionnaire was given to a convenience sample of female patients aged 18 to 50 years visiting 2 academic family medicine clinics in the southeastern United States. Descriptive statistics and logistic regression models were used for analysis. RESULTS A total of 178 women completed questionnaires. Nearly one-half (47%) of respondents believed that pregnancy begins with fertilization; however, less than one-third (30%) believed that life begins with fertilization. Thirty-eight percent of respondents stated that they would use EC only if they believed it worked before fertilization or implantation. Generally similar proportions thought that EC works before fertilization (24%) and before implantation (36%), or were unsure about when it works (34%). Younger age was associated with higher odds of believing that EC works before fertilization; none of the other demographic factors studied conferred either higher or lower odds. CONCLUSIONS Many women are uninformed about the possible mechanisms of action of EC, and we found no reliable predictors for those who were better informed. This study raises questions regarding women’s understanding of EC and demonstrates the need to better educate them about its possible mechanisms of action.